The potential impact of ash Merapi Volcano eruption 2010 in Yogyakarta, Indonesia, for the environment and human health - Wawan Budianta (Journal of Applied Geology, 2015)
The eruptions of Merapi Volcano began in late October 2010 and continued into early November 2010. Among parts of materials ejected by Merapi Volcano, volcanic ash is considered to be a respiratory health hazard because of several potentially toxic components: respirable crystalline silica and metals. The objective of this study is to review the grain size of volcanic ash and to analyze the composition of volcanic ash which is suspected to carry a variety of potentially toxic elements. The result of this study shows that very fine grain size of volcanic ash were detected which has a potential to become respiratory problem trigger. The heavy metals were also detected in ash samples. On the other hand, total sulfur content was also considered high and the source of this sulfur was sulfur dioxide during eruption. Keywords: Merapi volcano, eruption, volcanic ash, health hazard, toxic elements.